Foundations of heat transfer. - 4 0 16; Incropera, Frank P.,;Dewitt, David P.,;Bergman, T.L.,;Lavine, Adrienne S.; 5 (Singapore : John Wiley & Sons, 2013)
Provides engineers with an in-depth look at the key concepts in the field. It incorporates new discussions on emerging areas of heat transfer, discussing technologies that are related to nanotechnology, biomedical engineering and alternative energy.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Transmission. -- Heat;Mass transfer; 20; 2